The thousand faces of Dunjia [videorecording (DVD)] - Yuen, Wo-ping, 1945-; Dapeng, 1982-; Ni, Ni, 1988-; Rahman, Arif (Actor) (Well Go USA Entertainment, 2018)
A police officer discovers a secret society with supernatural abilities and joins them as they prepare to destroy an ancient creature.